Adaptation of Career Optimism Scale Using Confirmatory Factor Analysis (CFA) Method - Pertiwi, Mutiara Chandra; Rahmawati Prihastuty; Talitha Lintang Pertiwi; Chamilul Hikam Al Karim (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aimed to adapt the career optimism subscale of the Career Futures Inventory (CFI), developed by Rottinghaus dkk. (2005), into the Indonesian language. Career optimism is defined as a positive expectation regarding future career development. The adaptation process followed the International Test Commission (ITC) guidelines, including translation, expert content validation, and construct validity testing using Confirmatory Factor Analysis (CFA). A total of 320 participants were selected using a simple random sampling technique. The CFA results indicated that the unidimensional factor structure of the career optimism scale demonstrated good model fit (CFI = 0.961, TLI = 0.950, RMSEA = 0.080). In addition, the scale exhibited high reliability, with a Cronbach’s Alpha of 0.926. These findings indicate that the Indonesian version of the career optimism subscale is both valid and reliable for use in the Indonesian context. This measurement tool can be applied in psychological assessments, career counseling services, and further research on career optimism in Indonesia.